Implementation of Community Empowerment in Thematic Programs in Tidar Village, Tangerang City - Talakua, Decky Carste (Best Journal of Administration and Management, 2024)
The environmental problems we are experiencing now are a matter of healthy survival, harmony with nature and the continuation of peaceful life for generations. In reality, the pace of development does not seem to be able to escape environmental pollution, so that the earth's carrying capacity is increasingly decreasing. One of the Tangerang City government's innovations in overcoming the problem of slum settlements is through the "Thematic Village" program, specifically to improve the area and implement a clean and healthy lifestyle. The aim of this research is to answer questions about the analysis of community empowerment in the development of thematic villages in Tidar village, East Sudimara sub-district, Tangerang City, what are the obstacles and how to overcome them in the analysis of community empowerment in the development of thematic villages. The research method used in this research is a qualitative approach. The results of this research conclude that "Kampung Tidar" is a real manifestation of community empowerment which was initiated by the community itself and then supported and facilitated by the government.